Post Partum Uterine Prolapse In A Non-Descriptive Cow - Kumar, Pravesh; Kumar, Amit; Barman, Purabi; Singh, Madhumeet; Ranaut, Nishant (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Prolapse or eversion of the uterus is also called casting of "Wethers" or casting of the "Calf bed" (Roberts, 1971; Rebhun, 1995). Eversion of uterus has been encountered as a common reproductive emergency of the postpartum cow which needs immediate therapeutic management to avoid further complication (Arthur et al., 2001). Pluriparous cows are more often involved than heifers (Roberts, 1971). Atony of the reproductive tract and weakness of genital organs may predispose the condition but it is less commonly seen in pastured or grazing cattle than the stall fed or zero grazing animals. Uterine prolapse occurs within few hours after calving. The condition is invariably associated with hypocalcaemia, which results in lack of uterine tone and delayed cervical involution (Smith, 2009).